Long non‐coding RNA SNHG14 contributes to gastric cancer development through targeting miR‐145/SOX9 axis - Liu, Zhao; Yan, Yan; Cao, Sizhe; Chen, Yi (Journal of cellular biochemistry, 2018)
This study aimed to elucidate the roles of long non‐coding RNA SNHG14 in gastric cancer development. LncRNA SNHG14 was markedly up‐regulated in gastric cancer tissues and cells. Knockdown of SNHG14 significantly inhibited SGC‐7901 cell viability, migration, invasion, and promoted cell apoptosis. In addition, miR‐145 was negatively regulated by SNHG14 and the effects of SNHG14 knockdown on cell viability, apoptosis, migration, invasion, and the expression of apoptosis‐related proteins and EMT‐markers were reversed by inhibition of miR‐145 at the same time. Furthermore, SOX9 was verified as a functional target of miR‐145, and miR‐145 regulated tumor malignant behaviors through regulating SOX9. Besides, knockdown of SNHG14 inhibited the expression of p‐PI3 K, p‐AKT, and p‐mTOR and promoted PTEN expression, where miR‐145 inhibition had opposite effects. Moreover, the activated PI3 K/AKT/mTOR pathway caused by miR‐145 inhibition was counteracted after knockdown of SOX9. Our findings indicate that up‐regulation of lncRNA SNHG14 may contribute to gastric cancer development via targeting miR‐145/SOX9 axis and involving in PI3 K/AKT/mTOR pathway. SNHG14‐miR‐145/SOX9 axis may be a promising therapeutic strategy for gastric cancer treatment. Our study aimed to elucidate the roles of long non‐coding RNA SNHG14 in gastric cancer development. These findings indicate that up‐regulation of lncRNA SNHG14 may contribute to gastric cancer development via targeting miR‐145/SOX9 axis and involving in PI3K/AKT/mTOR pathway. SNHG14‐miR‐145/SOX9 axis may be a promising therapeutic strategy for gastric cancer treatment.